Tess of the d’Urbervilles du roman à l’écran : les ambiguïtés du point de vue - Isabelle Gadoin (Cahiers Victoriens et Edouardiens)
Even though the notion of « point of view » in fiction naturally involves a visual metaphor, the transposition of point of view appears to be one of the great challenges of adaptations of novels into films. Indeed, Hardy’s narrators, at least in his late fiction, are tantalisingly ambiguous, and tend to act in two highly contradictory ways : appealing to the reader’s sympathy and pity for the plight of the protagonist, while simultaneously undermining this involvement through the critical or ironical interventions of the obtrusive narrator. Hardy’s late fiction can definitely be labelled as « modern » in that it both encourages and defeats narrative illusion, particularly in Tess of the d’Urbervilles, which wavers between fleeting moments of identification with the heroine’s point of view (thanks to internal focalisation) and narratorial corrections of these subjective « moments of vision », to take up the title of later poems. This article tries to study some of the means of rendering this ambiguity on the screen, by various processes of « subjective images », but also points the limits of such adaptations : what the film seems to erase is the double-bind subtly created in the novel by the split between focalisation and narrative intervention. The comparison between text and image thus helps define some of the specificities of each medium.